Translational challenges for the development of a novel nucleus pulposus substitute: Experimental results from biomechanical and in vivo studies. (February 2016) - Detiger, SEL; de Bakker, JY; Emanuel, KS; Schmitz, M; Vergroesen, PPA; van der Veen, AJ; Mazel, C; Smit, TH
Nucleus pulposus replacement therapy could offer a less invasive alternative to restore the function of moderately degenerated intervertebral discs than current potentially destructive surgical procedures. Numerous nucleus pulposus substitutes have already been investigated, to assess their applicability for intradiscal use. Still, the current choice of testing methods often does not lead to efficient translation into clinical application. In this paper, we present the evaluation of a novel nucleus pulposus substitute, consisting of a hydromed core and an electrospun envelope. We performed three mechanical evaluations and an in vivo pilot experiment. Initially, the swelling pressure of the implant was assessed in confined compression. Next, we incorporated the implant into mechanically damaged caprine lumbar intervertebral discs to determine biomechanical segment behaviour in bending and torsion. Subsequently, segments were serially tested in native, damaged and repaired conditions under dynamic axial compressive loading regimes in a loaded disc culture system. Finally, nucleus pulposus substitutes were implanted in a live goat spine using a transpedicular approach. In confined compression, nucleus pulposus samples as well as implants showed some load-bearing capacity, but the implant exhibited a much lower absolute pressure. In bending and torsion, we found that the nucleus pulposus substitute could partly restore the mechanical response of the disc. During dynamic axial compression in the loaded disc culture system, on the other hand, the implant was not able to recover axial compressive behaviour towards the healthy situation. Moreover, the nucleus pulposus substitutes did not remain in place in the in vivo situation but migrated out of the disc area. From these results, we conclude that implants may mimic native disc behaviour in simple mechanical tests, yet fail in other, more realistic set-ups. Therefore, we recommend that biomaterials for nucleus pulposus replacement be tested in testing modalities of increasing complexity and in their relevant anatomical surroundings, for a more reliable prediction of clinical potential.